1. ![b^{2}+4+4b - 2b^{2} -2b=-b^{2}+2b+4\\\\ b^{2}+4+4b - 2b^{2} -2b=-b^{2}+2b+4\\\\](https://tex.z-dn.net/?f=b%5E%7B2%7D%2B4%2B4b%20-%202b%5E%7B2%7D%20%20-2b%3D-b%5E%7B2%7D%2B2b%2B4%5C%5C%5C%5C)
2.
x=3 \\x=0 и x=3\\b) 3-4(x+2)=5-6x \\3-4x-8-5+6x=0\\2x-10=0\\x=5\\" alt="a) x(6-2x)=0\\x=0 , 6-2x=0 => x=3 \\x=0 и x=3\\b) 3-4(x+2)=5-6x \\3-4x-8-5+6x=0\\2x-10=0\\x=5\\" align="absmiddle" class="latex-formula">
3.
\frac{-11}{13} \\(\frac{-11}{13}" alt="2-8x<3+5(x+2)\\-13x<11\\x>\frac{-11}{13} \\(\frac{-11}{13}" align="absmiddle" class="latex-formula"> ; +∞)